Detecting Direction And Numbers: Analysis Of Financial Literacy Levels In Bumdes In Ampana - Fera Fera; Anisah Anisah; Cici Rianty K. Bidin (UNIVED Press, 2025)
This study aims to analyze the level of financial literacy in Village-Owned Enterprises (BUMDes) in Ampana with a quantitative approach using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method using WarpPLS 8.0 software. The focus of this study is to detect the direction and number of influences of factors such as financial knowledge and financial attitudes on BUMDes financial literacy. The results of the study indicate that financial knowledge does not directly affect financial literacy, but does affect financial attitudes. Financial attitudes affect financial literacy. Financial attitudes are not significant as a moderating variable, but act as a mediating variable between Financial knowledge and financial literacy. This study contributes to improving financial literacy in BUMDes managers, which is expected to have a positive impact on better financial governance at the village level.